2018
DOI: 10.1590/0004-282x20170190
|View full text |Cite
|
Sign up to set email alerts
|

Naming and verbal learning in adults with Alzheimer's disease, mild cognitive impairment and in healthy aging, with low educational levels

Abstract: Language assessment seems to be an effective tool to differentiate healthy and cognitively impaired aging groups. This article discusses the impact of educational level on a naming task, on a verbal learning with semantic cues task and on the MMSE in healthy aging adults at three educational levels (very low, low and high) as well as comparing two clinical groups of very low (0-3 years) and low education (4-7 years) patients with Alzheimer's disease (AD) and mild cognitive impairment (MCI) with healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…It has also been shown that highly educated individuals produce higher type token ratios (Hübner et al, 2018) and larger number of unique words in tasks like verbal fluency (Kawano, Umegaki, Suzuki, Yamamoto, Mogi, & Iguchi, 2010), so it is important to control for factors such as socioeconomic status in any SLB data analysis. Some epidemiological studies have reported faster cognitive decline in more educated people (Teri, McCurry, Edland, Kukull, & Larson, 1995;Scarmeas, Albert, Manly, & Stern, 2006), whereas other studies report slower decline in individuals with Alzheimer's disease who have attained more education (Fritsch, McClendon, Smyth, & Ogrocki, 2002).…”
Section: : Offers New Health Information Including Common Confoundsmentioning
confidence: 99%
“…It has also been shown that highly educated individuals produce higher type token ratios (Hübner et al, 2018) and larger number of unique words in tasks like verbal fluency (Kawano, Umegaki, Suzuki, Yamamoto, Mogi, & Iguchi, 2010), so it is important to control for factors such as socioeconomic status in any SLB data analysis. Some epidemiological studies have reported faster cognitive decline in more educated people (Teri, McCurry, Edland, Kukull, & Larson, 1995;Scarmeas, Albert, Manly, & Stern, 2006), whereas other studies report slower decline in individuals with Alzheimer's disease who have attained more education (Fritsch, McClendon, Smyth, & Ogrocki, 2002).…”
Section: : Offers New Health Information Including Common Confoundsmentioning
confidence: 99%
“…A estratégia adotada foi solicitar que os pacientes elaborassem a narrativa a partir do input oferecido: um conjunto de 22 cenas representadas em figuras sobre a história infantil "Cinderela", as quais foram apresentadas numa determinada sequência. Para Para Hübner et al (2018), estudos sobre a linguagem têm mostrado ser uma 31 O recurso informático Coh-Metrix-Dementia foi utilizado para extração automática das métricas e os resultados identificados por grupos estudados. Foram feitas adaptações em relação à segmentação das sentenças para um melhor funcionamento da ferramenta computacional.…”
Section: Marcos Linguísticos Subjacentesunclassified